Reduction in power requirement and flow enhancement by reducing the inertia masses of reciprocating air compressor. (2023) - Kulkarni, Hrishikesh; Chavan, Sandip; Birari, Abhijeet; Pawar, Dipak
Abstract: Weight of reciprocating components in the design of a reciprocating compressor plays an important role. The reciprocating masses such as piston, piston rod, connecting rod, crosshead, etc in a reciprocating compressor results in inertia load on the compressor. The inertia load along with other loads like gas load and total load consumes the power from the electric motor to drive the compressor. To increase the flow, the rpm of the compressor must be increased. But as the rpm increases the inertia load also increases. Excess inertia load leads to failure of the piston rod and ultimately this leads to failure of the reciprocating compressor. Thus inertia load has its significance in the designing of reciprocating compressors. The aim of the research is to reduce the weight of the piston in a system of reciprocating masses and to study its effect on the power consumption, flow enhancement from the compressor and to analyze the piston assembly for safe design. The compressor under study is Kirloskar Pneumatic reciprocating air compressor. Weight reduction is achieved by changing the material of the piston from Al alloy to AZ91. Changing of the material resulted in a 20% reduction in power requirement during unloading condition. The flow of the compressor is increased by 9%. The piston assembly was modeled on Autodesk Inventor 2018 and analyzed in Ansys Workbench 19.0. Analysis of the piston made from Al alloy and AZ91 was done. The stresses induced in the piston were below the yield strength. Thus the piston was safe in design. Reduction in power requirement leads to reduction in operating cost of the compressor. More flow from the compressor gives it an added advantage for the compressors to be used for a broad range of applications with the same design.